2019
DOI: 10.1021/acsami.8b20180
|View full text |Cite
|
Sign up to set email alerts
|

High Active Magnesium Trifluoromethanesulfonate-Based Electrolytes for Magnesium–Sulfur Batteries

Abstract: The shortage of high-performance and easily prepared electrolyte has hindered the progress of rechargeable magnesium–sulfur (Mg–S) batteries. In this paper, we develop a new electrolyte based on Mg­(CF3SO3)2–AlCl3 dissolved in tetrahydrofuran and tetraglyme mixed solvents. Mg­(SO3CF3)2 as an Mg2+ source is nonnucleophilic, easy to handle, and much cheaper than Mg­(TFSI)2 (TFSI = bis­(trifluoromethanesulfonyl)­imide). After modification with anthracene (π stabilizing agent) as a coordinating ligand to stabilize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 52 publications
2
70
0
Order By: Relevance
“…Among all reported Mg–S batteries, currently used anode materials are mainly composed of metallic magnesium in form of magnesium discs, plates, ribbons, or foils . These types of anodes generally have a low surface area.…”
Section: Anode Materialsmentioning
confidence: 99%
See 4 more Smart Citations
“…Among all reported Mg–S batteries, currently used anode materials are mainly composed of metallic magnesium in form of magnesium discs, plates, ribbons, or foils . These types of anodes generally have a low surface area.…”
Section: Anode Materialsmentioning
confidence: 99%
“…In Mg–S batteries, the choice of the current collector has also a great impact on the electrochemical behavior particularly in the case of halogen‐containing corrosive electrolytes, the nature of the electroactive cathode materials and the dissolution of polysulfides during cycling . The currently reported commercial metal‐based current collectors include aluminum foil, stainless‐steel (SS) foil, carbon‐coated aluminum foil, copper, and the anticorrosion alloy Inconel 625 . While Cu is generally considered unstable against chloride‐containing electrolytes, Zeng et al recently reported that a sulfur cathode is compatible with the traditional APC electrolyte using copper as current collector below 1.7 V versus Mg/Mg 2+ .…”
Section: Cathode Materialsmentioning
confidence: 99%
See 3 more Smart Citations